ANALISIS USABILITY MEDIA PEMBELAJARAN INTERAKTIF LANGIT MAYA TENTANG CYBERBULLYING PADA SISWA KELAS VIII SMP NEGERI 15 MALANG - Latif, Rafika; Kirana, Kartika Candra; Purwanto, Eko Tristyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid advancement of digital technology has introduced various social challenges among adolescents, one of which is cyberbullying. Low levels of digital literacy and limited student understanding of this issue demand contextual and engaging learning innovations. This study aims to analyze the usability level of the interactive learning media Langit Maya, developed to deliver educational content about cyberbullying to eighth-grade students at SMP Negeri 15 Malang. This research employed a descriptive quantitative method using the System Usability Scale (SUS) instrument consisting of 10 Likert-scale statements. Data were collected from 30 students who used the media during a learning session and analyzed using the standard SUS calculation. The results showed that the average usability score of Langit Maya was 77.5, categorized as “Good” and “Acceptable.” Most students reported that the media was easy to use, comfortable, and effective in helping them understand the concept of cyberbullying. These findings indicate that Langit Maya possesses a high level of usability and can serve as an alternative digital learning tool that responds to the needs and characteristics of students in the digital age.